Pembrolizumab, radiotherapy, and an immunomodulatory five-drug cocktail in pretreated patients with persistent, recurrent, or metastatic cervical or endometrial carcinoma: Results of the phase II PRIMMO study - Emiel A. De Jaeghere; Sandra Tuyaerts; An M. T. Van Nuffel; Ann Belmans; Kris Bogaerts; Regina Baiden-Amissah; Lien Lippens; Peter Vuylsteke; Stéphanie Henry; Xuan Bich Trinh; Peter A. van Dam; Sandrine Aspeslagh; et al. (Cancer Immunology, Immunotherapy)
Abstract A phase II study (PRIMMO) of patients with pretreated persistent/recurrent/metastatic cervical or endometrial cancer is presented. Patients received an immunomodulatory five-drug cocktail (IDC) consisting of low-dose cyclophosphamide, aspirin, lansoprazole, vitamin D, and curcumin starting 2 weeks before radioimmunotherapy. Pembrolizumab was administered three-weekly from day 15 onwards; one of the tumor lesions was irradiated (8Gyx3) on days 15, 17, and 19. The primary endpoint was the objective response rate per immune-related response criteria (irORR) at week 26 (a lower bound of the 90% confidence interval [CI] of > 10% was considered efficacious). The prespecified 43 patients (cervical, n = 18; endometrial, n = 25) were enrolled. The irORR was 11.1% (90% CI 2.0–31.0) in cervical cancer and 12.0% (90% CI 3.4–28.2) in endometrial cancer. Median duration of response was not reached in both cohorts. Median interval-censored progression-free survival was 4.1 weeks (95% CI 4.1–25.7) in cervical cancer and 3.6 weeks (95% CI 3.6–15.4) in endometrial cancer; median overall survival was 39.6 weeks (95% CI 15.0–67.0) and 37.4 weeks (95% CI 19.0–50.3), respectively. Grade ≥ 3 treatment-related adverse events were reported in 10 (55.6%) cervical cancer patients and 9 (36.0%) endometrial cancer patients. Health-related quality of life was generally stable over time. Responders had a significantly higher proportion of peripheral T cells when compared to nonresponders (p = 0.013). In conclusion, PRIMMO did not meet its primary objective in both cohorts; pembrolizumab, radiotherapy, and an IDC had modest but durable antitumor activity with acceptable but not negligible toxicity. Trial registration ClinicalTrials.gov (identifier NCT03192059) and EudraCT Registry (number 2016-001569-97).